Alice i Vänsterlandet: Ett autoetnografiskt projekt som gick på grund - Liliequist, Marianne (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2011)
The article is about an auto-ethnographic project that collapsed. The project was meant to be an analysis of the author’s own journey into the world of left politics in the 1970’s. To make personal experiences the focus of cultural analysis felt like something very forbidden and at the same time very satisfying in a personal sense. The author brings forward the rewards that can be reached by auto-ethnographic methods, the rich context and involvement which can be expressed.